Immune responses to oligomeric α-synuclein in Parkinson’s disease peripheral blood mononuclear cells - Vega-Benedetti, Ana Florencia; Porcedda, Clara; Ercoli, Tommaso; Fusco, Giuliana; Burgaletto, Chiara; Pillai, Rita; Palmas, Francesca; Cantone, Anna Flavia; Angius, Fabrizio; Solla, Paolo; De Simone, Alfonso; Cantarella, Giuseppina; et al. (Journal of neurology, 2024)
Parkinson’s disease displays clinical heterogeneity, presenting with motor and non-motor symptoms. Heterogeneous phenotypes, named brain-first and body-first, may reflect distinct α-synuclein pathology starting either in the central nervous system or in the periphery. The immune system plays a prominent role in the central and peripheral pathology, with misfolded α-synuclein being placed at the intersection between neurodegeneration and inflammation. Here, we characterized the inflammatory profile and immune-phenotype of peripheral blood mononuclear cells (PBMCs) from Parkinson’s disease patients upon stimulation with α-synuclein monomer or oligomer, and investigated relationships of immune parameters with clinical scores of motor and non-motor symptoms. Freshly isolated PBMCs from 21 Parkinson’s disease patients and 18 healthy subjects were exposed in vitro to α-synuclein species. Cytokine/chemokine release was measured in the culture supernatant by Multiplex Elisa. The immune-phenotype was studied by FACS-flow cytometry. Correlation analysis was computed between immune parameters and parkinsonian motor and non-motor scales. We found that Parkinson’s disease patients exhibited a dysregulated PBMC-cytokine profile, which remained unaltered after exposure to α-synuclein species and correlated with both motor and non-motor severity, with a strong correlation observed with olfactory impairment. Exposure of PBMCs from healthy controls to α-synuclein monomer/oligomer increased the cytokine/chemokine release up to patient’s values. Moreover, the PBMCs immune phenotype differed between patients and controls and revealed a prominent association of the Mos profile with olfactory impairment, and of NK profile with constipation. Results suggest that a deranged PBMC-immune profile may reflect distinct clinical subtypes and would fit with the recent classification of Parkinson’s disease into peripheral-first versus brain-first phenotype.